Systematic Review: Android-Based Interactive Learning Media to Enhance Understanding of Islamic Education in Support of SDGs - Umi Basyiroh; Akhmad Arif Musadad; Moh. Muchtarom; Abu Zarrin bin Selamat (Universitas Muhammadiyah Surakarta, 2024)
Objective: The modern era necessitates the development of Islamic Religious Education (IRE) learning that is interactive and practical, aligning with digitalization trends and supporting the Sustainable Development Goals (SDGs) in quality education. However, traditional PAI learning often relies on one-way lectures, limiting student engagement and hindering conceptual understanding. This study aims to analyze the role of Android-based interactive learning media in enhancing students' comprehension of IRE concepts. Theoretical framework: The theoretical framework of this study is based on the constructivist learning theory, which emphasizes active student participation in the learning process. Additionally, cognitive load theory is considered, as interactive digital media can reduce extraneous cognitive load and facilitate meaningful learning. Literature Review: A literature review was conducted to explore previous studies on Android-based learning applications in religious education. Methods: This study employs a systematic literature review methodology, incorporating qualitative analysis to synthesize research findings from various academic sources. Results: Research findings indicate that interactive features such as videos, quizzes, and simulations significantly improve students' understanding and engagement in IRE subjects. Applications like Mobile Learning, RuBer IRE, and iSpring Suite provide creative and relevant learning experiences, aligning with the SDGs’ goal of inclusive and equitable quality education. The reviewed studies demonstrate that Android-based learning media enhances knowledge retention and critical thinking skills. However, challenges such as internet connectivity issues, data security, and students' technological proficiency must be addressed to maximize effectiveness. Implications: The study's implications highlight the need for educators and policymakers to integrate digital learning tools in Islamic education strategically. Novelty: This research offers novelty by emphasizing the intersection of Islamic education, interactive digital learning, and SDGs, showcasing how technology can bridge gaps in traditional religious instruction. Future studies should focus on empirical evaluations of Android-based media in diverse educational settings.